IMPLICATIONS FOR THE CORRELATION OF THE HELLENIC NAPPES IN SW AEGEAN: THE GEOLOGICAL STRUCTURE OF THE ARCHANGELOS REGION, RHODES ISLAND - Lekkas, E.; Danamos, G.; Skourtsos, E. (Bulletin of the Geological Society of Greece, 2007)
In the region of Archangelos in central-eastern Rhodes, a nappe sequence from bottom to top consists of i) Laerma unit, an Oligocene age wildflysch, ii) Archangelos unit, a neritic limestone of Upper Triassic - Mid Eocene age grading through red pelites to a flysch sequence, probably combarable to Ethia unit of Crete, iv) the Profus Ilias unit, a pelagic sequence ofplaty limestones and radiolarites of Upper Triassic - Upper Cretaceous age, similar to Pindos Unit and v) the ophiolites. The emplacement of the nappes on the relative autochthonous Laerma unit was carried out in surface conditions and is due to gravitational sliding estimated during Lower Oligocene to Middle - Upper Oligocene.